Bringing to Light Symptoms and Treatments of Effort Thrombosis (Paget–Schroetter Syndrome) in the Military Population, a Case Study. Issue 5 (1st May 2017) - Ringhouse, Brendan; Jackson, Cody
ABSTRACT: Background: Effort thrombosis, or Paget–Schroetter Syndrome, is an activity-induced upper extremity deep vein thrombosis affecting the axillary and/or subclavian vein. It is a rare disorder affecting 2 per 100, 000 person years and mainly occurring in young, active individuals after repetitive upper extremity exertion. Effective diagnosis and management of this disorder has been difficult to study given the syndrome's rarity. Methods: We discuss and evaluate the case of a 38-year-old muscular male Marine who presented to the primary care clinic following an incorrect diagnosis during an emergency room visit where he was evaluated and treated for a right pectoralis muscle strain while having symptoms suggestive of upper extremity vascular congestion, including pain and edema. Findings: Given this presentation in a concentrated population such as the military, the primary care provider's suspicion of effort thrombosis was heightened. This patient was directed for lab and radiology examination followed by vascular surgery evaluation to be treated with catheter-directed thrombolysis, anticoagulation, and a first rib resection. Discussion: Though rare, effort thrombosis is of particular importance in our relatively young, athletic population. A missed or delayed diagnosis could lead to lifelong disability. Awareness of this condition's presentation, inciting factors, and potential sequelae is important to minimize mortality and morbidity.